EL DIAGNOSTICO HISTOLOGICO POR ASPIRACIONBIOPSIA - CURIEL R (Sociedad Mexicana Historia Natural, CD MEXICO, DF, MEX, 1944)
Occurrence of fossil bats in the Eocene epoch is noted in the introduction, and bats are considered as living fossils; phylogenetic relations, special senses and the dental formula are discussed from this viewpoint Former histologic studies are reviewed
REV MEX MED
Keywords: DIAGNOSTICO, HISTOLOGICO, ASPIRACIONBIOPSIA; CIENCIAS MEDICAS; CIENCIAS CLINICAS; PATOLOCIA CLINICA